The Impact of Road Irregularities on the Motion of a Motor Vehicle during Acceleration - Jarosław Zalewski (Communications - Scientific letters of the University of Zilina, 2022)
In this paper the selected results concerning the analysis of the phenomena occurring between the road and the wheels of a motor vehicle have been presented. The analysis was prepared for the simulation of the acceleration maneuver with the 100% (full) throttle along the road with various conditions. The aim of this paper was to analyze whether both the full throttle and the road conditions may affect the forces occurring in the contact area between the wheels of the vehicle and the road, regarding the road conditions and the rear wheel drive of the analyzed vehicle’s model.